Lightweight high-strength fly ash and magnesium slag mixture ceramsite and preparation method thereof

By preparing lightweight high-strength fly ash and magnesium slag mixture ceramic granules, the problems of poor strength and complex process of existing fly ash building materials are solved, efficient utilization and environmental protection of fly ash are achieved, and high-strength light quartz concrete reduces the damage to the ecology caused by gravel mining.

CN119263871APending Publication Date: 2025-01-07HEBEI YAODI CONSTRUCTION ENGINEERING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411362743.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing fly ash building materials use cement as cementitious agent, the process is complex and the strength is poor, and the fly ash resources cannot be effectively utilized, resulting in increased environmental pollution and economic burden.

Method used

The preparation method of lightweight high-strength fly ash and magnesium slag mixture is prepared by grinding, digestion, homogenization, ball formation, resting and pressure kettle treatment, and the particle size is less than 30mm and the moisture content is less than 0.5%. and use it as light aggregate in concrete to replace gravel to form high-strength concrete.

Benefits of technology

It realizes efficient utilization of fly ash, reduces environmental pollution, reduces production costs, and provides high-strength lightweight concrete, avoids the ecological damage caused by gravel mining, and improves the waste utilization rate of enterprises.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263871A_ABST
    Figure CN119263871A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides lightweight high-strength fly ash and magnesium slag mixture ceramsite and a preparation method thereof. The preparation method comprises the steps that magnesium slag with the particle size smaller than 3 mm enters a pulverizer to be pulverized; the method comprises the following steps: continuously adding 90%-95% by mass of magnesium slag powder and 5%-10% by mass of hot water at the temperature of 95-100 DEG C into a stirrer for mixing, feeding the mixed material into a digestion bin for digestion for 30-60 minutes at the digestion temperature of 60-65 DEG C to prepare digested magnesium slag with the particle size of less than 1 mm and the water content of less than 2%; continuously adding 20%-30% by mass of digested magnesium slag, 67.5%-74% by mass of fly ash, 2%-5% by mass of desulfurized gypsum and 0.5%-1% by mass of an activating agent into a pulverizer; the residue on a 325-mesh sieve is within 15%, and the water content is lower than 0.5%; then homogenizing, balling, coating and standing are conducted, the prepared light-weight and high-strength fly ash ceramsite is light in weight and high in strength, meanwhile, the mixing amount of fly ash is large, the utilization rate is high, and environmental protection is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of resource utilization of inorganic solid waste, and in particular to a lightweight high-strength fly ash plus magnesium slag mixture ceramsite and a preparation method thereof. Background Art

[0002] Thermal power plants of all sizes and other coal-consuming enterprises throughout my country produce a large amount of fly ash every year. In addition, the failure to deal with it in time over the years has caused harm to the environment. The increasing amount of ash has also caused a huge economic burden on the enterprises. The development of a product with a large amount of fly ash can not only turn fly ash into treasure and make full secondary utilization of it, but also reduce the burden of ash-discharging enterprises and the production costs of ash-using enterprises, but also greatly reduce the degree of pollution to the environment. In recent years, some building materials with fly ash as raw material have appeared in my country. However, the existing fly ash building materials generally use cement as a binder, and most of the raw material components are more than six, the process is relatively complicated, and its strength is poor. Summary of the invention

[0003] In view of this, the embodiments of the present application provide a lightweight and high-strength fly ash and magnesium slag mixture ceramsite and a preparation method to solve the above-mentioned technical problems existing in the prior art.

[0004] According to the first aspect of the present application, a method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite is provided, comprising:

[0005] Step 1: Put magnesium slag with a particle size less than 3 mm into a grinding mill for grinding;

[0006] Step 2: Add magnesium slag powder and 95-100 degree hot water in a mixer according to 90%-95% magnesium slag powder and 5%-10% hot water by mass, and send the mixed material into a digestion bin for digestion. The digestion time is 30-60 minutes and the digestion temperature is 60-65°C to obtain a digested magnesium slag with a particle size of less than 1 mm and a moisture content of less than 2%;

[0007] Step 3, continuously adding 20%-30% by mass of digested magnesium slag, 67.5%-74% of fly ash, 2%-5% of desulfurized gypsum and 0.5%-1% of activator into a grinding mill; obtaining a powder with a 325 mesh sieve residue of less than 15% and a moisture content of less than 0.5%;

[0008] Step 4: continuously mix and stir the powder obtained in step 3 with water at a temperature of 15%-20% in the ratio of 80%-85% of the powder to 15%-20% of the water to obtain powder pellets with a particle size of less than 30 mm;

[0009] Step 5, the powder pellets obtained in step 4 are put into a homogenizing device for homogenization to obtain a homogenized material with a 0.6 mm sieve residue of less than 15% and a fluffy appearance;

[0010] Step 6: The homogenized material obtained in step 5 enters a ball-forming machine for ball-forming. Fly ash is placed in the ball-forming machine. Water mist is sprayed during the ball-forming process. The water mist is sprayed to the boundary between the ash and the ball and above the moving center of the ball. The water mist level requirement is that the spray amount is 1-5% of the dry ash amount of the ball. The ball output requirement is that a 10mm ball falls freely from a height of 1 meter and hits a 10mm thick rubber plate twice without falling apart. The balls do not stick to each other, and no clear water can be seen on the surface of the ball by visual inspection.

[0011] Step 7. The balls from the ball forming machine enter the coating machine, and the ground fly ash is added at the same time. The ratio of balls to dry fly ash is 85%-95% by mass of balls and 5%-15% by mass of dry fly ash. The dry fly ash is added in a dispersed manner, and the adding position is 0.5-1 meter from the ball inlet. The requirements for the balls are that there is no clear water on the surface of the balls, there is a slight water mark on the ball when it is placed on the hand, and the 10mm ball falls freely from a height of 1 meter and hits a 10mm rubber plate 3 times without falling apart;

[0012] Step 8: Screen out the balls with a particle size of more than 19mm, and put the rest of the balls into the curing machine for curing; the height of the balls just entering should be less than 1 meter, and the height of the balls after 12 hours of curing should be less than 2 meters. The curing conditions are: the temperature is 35-45 degrees and the humidity is above 95 degrees in the first 6 hours, and the spray is sprayed until the surface of the balls is moistened visually in the last 18 hours. The cylinder pressure strength of the balls is greater than 4.0MPa.

[0013] Step nine, the balls obtained in step eight are placed in a pressure autoclave, the falling height of the balls entering the autoclave is less than 5 meters, the saturated steam enters the design pressure for 1.5-2.5 hours, reacts for 4-5 hours under the condition of saturated steam constant pressure of 1.0MPa, the exhaust time of the pressure autoclave is 2-3 hours, and a lightweight and high-strength fly ash ceramsite finished product is obtained.

[0014] In some embodiments, the magnesium slag powder with a particle size less than 1.18 mm is obtained in step 1.

[0015] In some embodiments, in step 2, the magnesium slag powder is first stirred for 2-3 minutes, and then the measured water is added for 5-7 minutes.

[0016] In some embodiments, the powder pellets prepared in step 4 are allowed to stand for 2-3 hours.

[0017] In some embodiments, the homogenized material prepared in step 5 is allowed to stand for 2-3 hours.

[0018] In some embodiments, it also includes:

[0019] The finished lightweight high-strength fly ash ceramsite obtained in step nine is graded according to the specification requirements of 1.18mm-4.75mm, 4.75mm-9.5mm, and 9.5mm-19mm to obtain finished lightweight high-strength fly ash ceramsite of different specifications.

[0020] According to a second aspect of the present application, there is provided a lightweight high-strength fly ash ceramsite prepared according to the method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite according to the first aspect.

[0021] In the third aspect of the present application, a method for preparing expanded clay concrete using the lightweight high-strength fly ash expanded clay described in the second aspect is provided, wherein the mix ratio is 450 kg of cement, 50 kg of silica fume, 462 kg of expanded clay, 738 kg of sand, 150 kg of water, and 0.58 kg of water reducer per cubic meter of concrete.

[0022] The lightweight high-strength fly ash and magnesium slag mixture ceramsite and its preparation method in the embodiment of the present application can be used as a lightweight aggregate in concrete to replace the stones in ordinary concrete, thereby preparing lightweight and high-strength concrete, which can be used for load-bearing structures, thereby avoiding the mining of stones in ordinary concrete, which requires blasting rocks, causing vegetation destruction, soil erosion, and causing serious damage to the ecological environment. At the same time, the fly ash is used to prepare ceramsite, and the fly ash dosage is large and the utilization rate is high. For power plants and other enterprises, it solves the problem of waste stacking, increases the benefits of additional products, and protects the environment at the same time.

[0023] It should be understood that the contents described in the Summary of the Invention are not intended to limit the key or important features of the embodiments of the present application, nor are they intended to limit the scope of the present application. Other features of the present application will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a process flow chart of the method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite according to Example 1 of the present application. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] In addition, the term "and / or" in this article is only a description of the association relationship between the associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0027] Figure 1 The process flow chart of the preparation method of lightweight high-strength fly ash and magnesium slag mixture ceramsite of Example 1 of the present application. The present application embodiment provides a method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite, comprising the following steps:

[0028] Step 1: Put magnesium slag with a particle size less than 3 mm into a grinding mill for grinding;

[0029] Step 2: 90%-95% magnesium slag powder and 5%-100 degree hot water are continuously added into a mixer for mixing according to the mass fraction, and the mixed material is sent into a digestion bin for digestion. The digestion time is 30-60 minutes and the digestion temperature is 60-65°C to obtain digested magnesium slag with a particle size of less than 1mm and a moisture content of less than 2%. Appropriate pre-wetting can reduce the water absorption rate of ceramsite, thereby reducing the shrinkage of ceramsite to ensure that it has good thermal insulation performance, and at the same time, it can remove impurities and dust on the surface of ceramsite and reduce its water absorption rate.

[0030] Step 3, continuously adding 20%-30% by mass of digested magnesium slag, 67.5%-74% of fly ash, 2%-5% of desulfurized gypsum and 0.5%-1% of activator into a grinding mill; obtaining a powder with a 325 mesh sieve residue of less than 15% and a moisture content of less than 0.5%;

[0031] Step 4: continuously mix and stir the powder obtained in step 3 with water at a temperature of 15%-20% in the ratio of 80%-85% of the powder to 15%-20% of the water to obtain powder pellets with a particle size of less than 30 mm;

[0032] Step 5, the powder pellets obtained in step 4 are put into a homogenizing device for homogenization to obtain a homogenized material with a 0.6 mm sieve residue of less than 15% and a fluffy appearance;

[0033] Step 6: The homogenized material obtained in step 5 enters a ball-forming machine for ball-forming. Fly ash is placed in the ball-forming machine. Water mist is sprayed during the ball-forming process. The water mist is sprayed to the boundary between the ash and the ball and above the moving center of the ball. The water mist level requirement is that the spray amount is 1-5% of the dry ash amount of the ball. The ball output requirement is that a 10mm ball falls freely from a height of 1 meter and hits a 10mm thick rubber plate twice without falling apart. The balls do not stick to each other, and no clear water can be seen on the surface of the ball by visual inspection.

[0034] Step 7. The balls from the ball forming machine enter the coating machine, and the ground fly ash is added at the same time. The ratio of balls to dry fly ash is 85%-95% by mass of balls and 5%-15% by mass of dry fly ash. The dry fly ash is added in a dispersed manner, and the adding position is 0.5-1 meter from the ball inlet. The requirements for the balls are that there is no clear water on the surface of the balls, there is a slight water mark on the ball when it is placed on the hand, and the 10mm ball falls freely from a height of 1 meter and hits a 10mm rubber plate 3 times without falling apart;

[0035] Step 8: Screen out the balls with a particle size of more than 19mm, and put the rest of the balls into the curing machine for curing; the height of the balls just entering should be less than 1 meter, and the height of the balls after 12 hours of curing should be less than 2 meters. The curing conditions are: the temperature is 35-45 degrees and the humidity is above 95 degrees in the first 6 hours, and the spray is sprayed until the surface of the balls is moistened visually in the last 18 hours. The cylinder pressure strength of the balls is greater than 4.0MPa.

[0036] Step nine, the balls obtained in step eight are placed in a pressure autoclave, the falling height of the balls entering the autoclave is less than 5 meters, the saturated steam enters the design pressure for 1.5-2.5 hours, reacts for 4-5 hours under the condition of saturated steam constant pressure of 1.0MPa, the exhaust time of the pressure autoclave is 2-3 hours, and a lightweight and high-strength fly ash ceramsite finished product is obtained.

[0037] In this embodiment, the magnesium slag can also be pre-classified and classified into particles with a size of less than 3 mm and particles with a size of more than 3 mm. The particles with a size of less than 3 mm enter a grinding mill, and the particles with a size of more than 3 mm enter a crusher for crushing. The magnesium slag can be crushed to a particle size of less than 1.18 mm, and then the magnesium slag with a particle size of less than 3 mm that has been classified and the magnesium slag with a particle size of less than 1.18 mm after crushing are mixed to be used for the magnesium slag with a particle size of less than 3 mm in step one of the embodiment of the present application.

[0038] In the magnesium slag of this embodiment, the mass proportion of iron ore powder impurities is less than or equal to 3%, the mass proportion of CaO is greater than or equal to 45%, and the mass proportion of magnesium oxide is less than or equal to 10%. The activator in this embodiment is an alkaline earth metal cation, and the material can be calcium chloride (CaCl2) or barium chloride (BaCl2).

[0039] In order to verify the strength of the fly ash ceramsite finished product of the embodiment of the present application, the following comparative experiment was designed:

[0040]

[0041] From the above experimental data, it can be known that increasing the content of CaO can improve the strength of the finished fly ash ceramsite, that is, in the process of preparing fly ash ceramsite, the proportion of fly ash added should not be too high. From the three groups of experimental data A, B, and C, it can be known that when the proportion of fly ash added in the process of preparing fly ash ceramsite is too high (54%-79%), the strength of the fly ash ceramsite obtained is low. The reason is that the fly ash is excessive, and some fly ash does not react with other raw materials. The fly ash ceramsite obtained only has fly ash under the bonding effect of water, resulting in low strength of the fly ash ceramsite. From the two groups of experimental data C and D, it can be known that when the proportion of fly ash added in the process of preparing fly ash ceramsite is reduced to 44%, the strength of the fly ash ceramsite obtained is significantly improved. The reason is that the fly ash reacts completely with other raw materials and there is almost no unreacted fly ash. It can be seen from the experimental data of groups D and E that when the proportion of fly ash added in the process of preparing fly ash ceramsite is lower than 44%, the strength of the prepared fly ash ceramsite will no longer be significantly improved. Under the premise of meeting the basic requirements, the cost will increase, and the cost of CaO is much higher than the cost of fly ash.

[0042] As a preferred embodiment of the present application, in the above embodiment, magnesium slag powder with a particle size less than 1.18 mm is obtained in step 1.

[0043] As a preferred embodiment of the present application, in the above embodiment, in step 2, the magnesium slag powder is first stirred for 2-3 minutes, and then the measured water is added for 5-7 minutes.

[0044] As a preferred embodiment of the present application, in the above embodiment, the powder pellets prepared in step 4 are allowed to stand for 2-3 hours.

[0045] As a preferred embodiment of the present application, in the above embodiment, the homogenized material obtained in step five is allowed to stand for 2-3 hours.

[0046] As a preferred embodiment of the present application, in the above embodiment, the lightweight high-strength fly ash ceramsite finished product obtained in step nine is graded according to the specification requirements of 1.18mm-4.75mm, 4.75mm-9.5mm, and 9.5mm-19mm to obtain lightweight high-strength fly ash ceramsite finished products of different specifications.

[0047] In addition, the present application also provides a lightweight high-strength fly ash ceramsite prepared by the method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite of the above embodiment.

[0048] The lightweight high-strength fly ash ceramsite prepared by the preparation method of the lightweight high-strength fly ash and magnesium slag mixture ceramsite of the present application can be used as a lightweight aggregate in concrete to replace the stones in ordinary concrete, thereby preparing lightweight and high-strength concrete, which can be used for load-bearing structures, thereby avoiding the mining of stones in ordinary concrete, which requires blasting rocks, causing vegetation destruction, soil erosion, and causing serious damage to the ecological environment. At the same time, the fly ash is used to prepare ceramsite, and the fly ash dosage is large and the utilization rate is high. For power plants and other enterprises, it solves the problem of waste stacking, increases the benefits of additional products, and protects the environment at the same time.

[0049] In addition, in order to verify the feasibility of using fly ash ceramsite to replace stone, the applicant also verified the proportion of ceramsite concrete materials through experiments. The raw materials of ceramsite concrete include cement, silica fume, fly ash ceramsite, medium sand with a fineness modulus of 2.6 and water reducing agent.

[0050] Among them, the performance of fly ash ceramsite is shown in the following table:

[0051]

[0052] Fly ash ceramsite was selected as coarse aggregate instead of stone, cement and silica fume were used as main gel materials, sand was used as fine aggregate, and water reducing agent was used to prepare ceramsite concrete. The experiment was divided into the following three groups:

[0053]

[0054]

[0055] Due to the loose and porous characteristics of ceramsite, it has high water absorption. Therefore, it is necessary to pre-wet the ceramsite before preparing ceramsite concrete. Soak the ceramsite in water for 1 hour, then take out the ceramsite and drain it to the saturated surface dry state, and then mix the ceramsite concrete. The preparation process of ceramsite concrete is as follows: first add cement, silica fume and sand and stir for 1 minute to mix them evenly; then add the pre-wetted ceramsite and gravel, stir for 2 minutes, so that the cementitious material can well wrap the ceramsite and gravel, and finally mix the water and water reducer evenly and add them, stirring for 2 minutes. Put the prepared ceramsite concrete into a 100mm×100mm×100mm mold, and after demolding, cure it in a standard curing room with a temperature of (20±2)℃ and a relative humidity greater than 95% for 28 days, and then conduct dry apparent density and compressive strength tests.

[0056] The dry apparent density and compressive strength of ceramsite concrete with different mix ratios were tested under standard curing for 28 days. The test results are as follows:

[0057]

[0058] There are a large number of pores inside the expanded clay, which has a "micro-pump" effect of absorbing and releasing water. After pre-wetting treatment, the expanded clay will release its internal moisture in the later stage, further allowing the cement in the expanded clay concrete to be fully hydrated and produce more hydration products, thereby improving its compressive strength. This is the reason why it is feasible to use expanded clay instead of stone.

[0059] Comparing the experimental data of groups F, G, and H, we can know that adding an appropriate amount of silica fume can improve the compressive strength of ceramsite concrete, but the silica fume dosage should not be too high. This is because silica fume is a good volcanic ash material. When it is compounded with cement, it will produce a volcanic ash effect while giving full play to the micro-aggregate effect, which can effectively fill the voids inside the concrete, thereby increasing the strength of ceramsite concrete; but when the silica fume dosage is too high, there will be unreacted admixtures inside the concrete, resulting in a decrease in strength.

[0060] Through the design of the mix ratio of ceramsite concrete, practical test, test block production, specimen curing and specimen testing, the test results of different mix ratios of different types of ceramsite concrete are analyzed, and the wide application of ceramsite market materials is compared. Combined with the market prices of various raw materials and the compressive strength performance of ceramsite concrete, fly ash high-strength ceramsite B.2 group is finally selected. Its mix ratio is 450kg of cement, 50kg of silica fume, 462kg of ceramsite, 738kg of sand, 150kg of water, and 0.58kg of water reducer per cubic meter of concrete. The test results show that the compressive strength of ceramsite concrete reaches 52.0MPa after 28 days of standard curing, the dry apparent density is 1945.5kg / m3, and the density grade of ceramsite concrete is 1900. After the test, it is known that the quality effect and economic effect of the verification result of this mix ratio design are better than other test groups and can meet the needs.

[0061] The above experiments can prove that expanded clay concrete can be used in building load-bearing structures, and has excellent properties such as light weight and high strength, thermal insulation, earthquake resistance and durability. Therefore, it has broad application areas and market prospects in the construction field.

[0062] The above specific implementations do not constitute a limitation on the protection scope of this application. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modifications, equivalent substitutions and improvements made within the spirit and principles of this application should be included in the protection scope of this application.

Claims

1. A method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite, characterized in that: include: Step 1: Put magnesium slag with a particle size less than 3 mm into a grinding mill for grinding; Step 2: Add magnesium slag powder and 95-100 degree hot water in a mixer according to 90%-95% magnesium slag powder and 5%-10% hot water by mass, and send the mixed material into a digestion bin for digestion. The digestion time is 30-60 minutes and the digestion temperature is 60-65°C to obtain a digested magnesium slag with a particle size of less than 1 mm and a moisture content of less than 2%; Step 3, continuously adding 20%-30% by mass of digested magnesium slag, 67.5%-74% of fly ash, 2%-5% of desulfurized gypsum and 0.5%-1% of activator into a grinding mill; obtaining a powder with a 325 mesh sieve residue of less than 15% and a moisture content of less than 0.5%; Step 4: continuously mix and stir the powder obtained in step 3 with water at a temperature of 15%-20% in the ratio of 80%-85% of the powder to 15%-20% of the water to obtain powder pellets with a particle size of less than 30 mm; Step 5, the powder pellets obtained in step 4 are put into a homogenizing device for homogenization to obtain a homogenized material with a 0.6 mm sieve residue of less than 15% and a fluffy appearance; Step 6: The homogenized material obtained in step 5 enters a ball-forming machine for ball-forming. Fly ash is placed in the ball-forming machine. Water mist is sprayed during the ball-forming process. The water mist is sprayed to the boundary between the ash and the ball and above the moving center of the ball. The water mist level requirement is that the spray amount is 1-5% of the dry ash amount of the ball. The ball output requirement is that a 10mm ball falls freely from a height of 1 meter and hits a 10mm thick rubber plate twice without falling apart. The balls do not stick to each other, and no clear water can be seen on the surface of the ball by visual inspection. Step 7. The balls from the ball forming machine enter the coating machine, and the ground fly ash is added at the same time. The ratio of balls to dry fly ash is 85%-95% by mass of balls and 5%-15% by mass of dry fly ash. The dry fly ash is added in a dispersed manner, and the adding position is 0.5-1 meter from the ball inlet. The requirements for the balls are that there is no clear water on the surface of the balls, there is a slight water mark on the ball when it is placed on the hand, and the 10mm ball falls freely from a height of 1 meter and hits a 10mm rubber plate 3 times without falling apart; Step 8: Screen out the balls with a particle size of more than 19mm, and put the rest of the balls into the curing machine for curing; the height of the balls just entering should be less than 1 meter, and the height of the balls after 12 hours of curing should be less than 2 meters. The curing conditions are: the temperature is 35-45 degrees and the humidity is above 95 degrees in the first 6 hours, and the spray is sprayed until the surface of the balls is moistened visually in the last 18 hours. The cylinder pressure strength of the balls is greater than 4.0MPa. Step nine, the balls obtained in step eight are placed in a pressure autoclave, the falling height of the balls entering the autoclave is less than 5 meters, the saturated steam enters the design pressure for 1.5-2.5 hours, reacts for 4-5 hours under the condition of saturated steam constant pressure of 1.0MPa, the exhaust time of the pressure autoclave is 2-3 hours, and a lightweight and high-strength fly ash ceramsite finished product is obtained.

2. The method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite according to claim 1, characterized in that: In step 1, magnesium slag powder with a particle size less than 1.18 mm is obtained.

3. The method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite according to claim 1, characterized in that: In step 2, the magnesium slag powder is first stirred for 2-3 minutes, and then the measured water is added for 5-7 minutes.

4. The method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite according to claim 1, characterized in that: The powder pellets prepared in step 4 are allowed to stand for 2-3 hours.

5. The method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite according to claim 1, characterized in that: The homogenized material prepared in step 5 is allowed to stand for 2-3 hours.

6. The method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite according to claim 1, characterized in that: Also includes: The finished lightweight high-strength fly ash ceramsite obtained in step nine is graded according to the specification requirements of 1.18mm-4.75mm, 4.75mm-9.5mm, and 9.5mm-19mm to obtain finished lightweight high-strength fly ash ceramsite of different specifications.

7. Lightweight high-strength fly ash and magnesium slag mixture ceramsite prepared according to the method for preparing lightweight high-strength fly ash and magnesium slag mixture ceramsite according to any one of claims 1 to 6.

8. A method for preparing ceramsite concrete using the lightweight high-strength fly ash and magnesium slag mixture ceramsite according to claim 7, characterized in that: The mix ratio is 450kg of cement, 50kg of silica fume, 462kg of expanded clay, 738kg of sand, 150kg of water and 0.58kg of water reducer per cubic meter of concrete.

Citation Information

Patent Citations

  • Method for preparing autoclaved brick by using refined magnesium slags and fly ash

    CN102225852A

  • Light magnesium slag building material and preparation method thereof

    CN111875410A

  • All-solid-waste-based high-strength mine filling cementing material and preparation method thereof

    CN115784703A

  • High-performance ceramsite for lightweight aggregate concrete prefabricated component and preparation method of high-performance ceramsite

    CN117003502A

  • Method for fabrication of light weight aggregate

    KR1020140108799A